Climatic classification and ordination of the Spanish Sistema Central: relationships with potential vegetation (Plant Ecology, 1998)
Monthly precipitation and monthly mean temperature records from 255 meteorological stations in Central Spain (Spanish Sistema Central) were analyzed by cluster and principal component analyses. Classiﬁcation separated 14 groups according to altitude, geographical distribution, as well as the combination of rainfall and temperature. The ﬁrst cluster emerged as signiﬁcantly higher and colder than the second. Then, two ordinations were carried out: one for the 14 groups extracted from the classiﬁcation and a second for the total station pool. The second ordination was compared with potential natural vegetation data taken around each station. The ﬁrst ordination summarized the principal climatic characteristics of the Spanish Sistema Central: its behaviour is that of a typical Mediterranean mountainous territory combining summer aridity and variation of temperature with altitude and the inﬂuence of winter winds. The ordination of all stations reﬂected a thermal, rainfall and summer aridity gradient. Meteorological stations situated at the highest altitude or with highest precipitation records characterized by scrub communities or pine woods and Quercus pyrenaica forests, appeared well-separated along the ﬁrst two axes. Only the most thermophilous Q. rotundifolia associations could be clearly separated. The fourth axis was useful in clarifying some vegetation overlap of deciduous and sclerophyllous forests, along an east-west summer aridity gradient.